2020
DOI: 10.1097/mpg.0000000000002711
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analyzers Are Suited for Diagnosing Celiac Disease Without a Biopsy

Abstract: Objectives: The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) 2012 guidelines, enabled for the first time, a nonbiopsy approach in the diagnosis of celiac disease (CD). We aimed to prospectively assess 4 tissue-transglutaminase (tTg) IgA assays of 4 random-access analyzers and examine their accuracy in diagnosing CD without a biopsy. Methods: We enrolled 186 consecutive children referred to upper endoscopy and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…In one such study, the no-biopsy algorithm showed a positive predictive value of 0.988 and a negative predictive value of 0.958 [41]. This and similar recent observations [60,61] led to rea rmation and further extension of no-biopsy approach to include asymptomatic children as well [12].…”
Section: European Movement Towards No-biopsysupporting
confidence: 70%
“…In one such study, the no-biopsy algorithm showed a positive predictive value of 0.988 and a negative predictive value of 0.958 [41]. This and similar recent observations [60,61] led to rea rmation and further extension of no-biopsy approach to include asymptomatic children as well [12].…”
Section: European Movement Towards No-biopsysupporting
confidence: 70%
“…In one such study, the nobiopsy algorithm showed a positive predictive value of 0.988 and a negative predictive value of 0.958 [41]. This and similar recent observations [60,61] led to rea rmation and further extension of no-biopsy approach to include asymptomatic children as well [12].…”
Section: European Movement Towards No-biopsysupporting
confidence: 69%
“…In one such study, the no-biopsy algorithm showed a positive predictive value of 0.988 and a negative predictive value of 0.958 [41]. This and similar recent observations [60,61] led to reaffirmation and further extension of no-biopsy approach to include asymptomatic children as well [12].…”
Section: European Movement Towards No-biopsysupporting
confidence: 65%